2021
DOI: 10.1029/2021jf006092
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Coastal Sand Deposits From Tsunamis and Storm Waves Based on Numerical Computations

Abstract: Paleotsunami sand deposits are useful for identifying frequency and magnitude of past tsunami events (e.g., G. A. Dawson & Shi, 2000) and consequently serve as a proxy for imminent threat arising from possible future events. Similarly, storm deposits can provide evidence of past catastrophic coastal storms (Morton & Sallenger, 2003). However, both tsunamis and storm waves can form similar deposits (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Even if energetic IG waves are generated, storm boulder transport distances are smaller than tsunami boulder transport distances in both the planar and reef topographies (Figure 2), as in the case of sand deposits (e.g., Watanabe et al., 2021). Thus, a longer transport distance can be crucial in differentiating tsunami and storm boulders, even if energetic IG waves are generated.…”
Section: Discussionmentioning
confidence: 99%
“…Even if energetic IG waves are generated, storm boulder transport distances are smaller than tsunami boulder transport distances in both the planar and reef topographies (Figure 2), as in the case of sand deposits (e.g., Watanabe et al., 2021). Thus, a longer transport distance can be crucial in differentiating tsunami and storm boulders, even if energetic IG waves are generated.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of coastal topography in STM was emphasized using 2D modeling with different slopes (Gusman et al., 2012; Watanabe et al., 2021). The I and S areas have different coastal topography on the coastline, beach ridge height, and the river mouth (Figures 1e and 1f).…”
Section: Discussionmentioning
confidence: 99%
“…STM is affected by topographic and sediment conditions, in addition to the wave height (Apotsos, Gelfenbaum, et al., 2011; Gusman et al., 2012, 2018; Li et al., 2012, 2014; Sugawara, 2019; Sugawara, Takahashi, & Imamura, 2014, 2019; Watanabe et al., 2017, 2021). Therefore, we performed sensitivity tests in the realistic parameter ranges that may have affected STM (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used 0.2 mm (2.0 phi) for sand sediment, the intermediate value of the observed grain size for sand deposits. Indeed, many previous studies simulated sediment transport using a single grain size and revealed that such simulation could explain the observed distribution (e.g., Apotsos et al., 2011a, 2011b; Sugawara et al., 2014; Watanabe et al., 2018, 2021). The observed grain size of the mud tsunami deposit in the Sendai plain is 4.0–6.82 phi (Chagué‐Goff et al., 2012).…”
Section: Methodsmentioning
confidence: 96%